2007
DOI: 10.1002/j.0022-0337.2007.71.2.tb04276.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student Dentist Competencies and Perception of Difficulty in Delivering Care to Children with Developmental Disabilities Using a Virtual Patient Module

Abstract: An interactive, multimedia, virtual patient module was designed and developed on compact disc (CD-ROM) to address the need for student dentists to increase their competence and decrease their perception of difficulty in caring for children with developmental disabilities. A development team consisting of pediatric dentistry faculty members, parents of children with developmental disabilities, an individual with a developmental disability, and educational specialists developed an interactive virtual patient cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 13 publications
0
64
1
Order By: Relevance
“…With all these things under consideration, we can conclude that much remains to be done in preparing general dentist in special care dentistry ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…With all these things under consideration, we can conclude that much remains to be done in preparing general dentist in special care dentistry ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Educational tools such as an informational DVD used in the present study are one of the ways in which the dental and medical fields can collaborate in the attempt to ensure persons with SHCN are receiving necessary oral health care. Virtual patient module with interactive multimedia which communicates and targets the need for dental student to decrease their perception of difficulty in caring for children with disabilities and to increase their competence is potentially an effective tool in meeting this need [ 28 ]. Also, in the present study, students indicated that the following would improve their ability to provide oral health care for persons with SHCN: further training, further education having equipment or products designed for persons with SHCN, continuing education related to oral health care for persons with SHCN, curriculum modification, and clinical case presentations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared use of a VP to no intervention. Eight of these showed significant differences favouring the VP intervention, including six studies looking at knowledge outcomes 15–20 and two looking at skills assessed through live patient encounters 21 or self‐report 22 . Four studies found results favouring the VP that did not reach statistical significance 23–26 .…”
Section: Research On Virtual Patientsmentioning
confidence: 99%
“…Some VPs have been used to develop a core fund of conceptual knowledge – an understanding of basic principles that undergird the practice of medicine 15,17–20,29,30 . Although VPs are clearly successful in achieving this objective, we wonder if other methods might be more economical, yet equally effective.…”
Section: Important Questions Regarding the Use Of Virtual Patientsmentioning
confidence: 99%